Miracle at St. Andrews [compact disc, unabridged] : a novel - Patterson, James, 1947-; De Jonge, Peter (Hachette Audio, 2019)
Former professional golfer Travis McKinley travels to Scotland to the mythical greens at St. Andrews in search of something that can help him achieve a higher plane.